Effect of aging on hardness in the upsetting tests using experimental and finite element investigations. (December 2017) - Hari Krishna, Ch; Davidson, MJ; Nagaraju, Ch
This paper investigates the hardness distribution in cold upsetting operation of the aged billets. Three sets of cylindrical billets were solutionized at 504 ℃ and then each set of billets were aged at 150 ℃ for a period of 9 h, 13 h, and 18 h, respectively. The billets were upset to different levels of strain and flow stress equation was evaluated for all the aging conditions. The flow stress equation was given as input to the finite element software and simulated to the same level of strain as in the case of experiments. An attempt to predict metal hardness was made by correlating the equivalent strain with the hardness. The hardness measurements predicted were in good agreement with the experimental results. The demand for producing billets with more hardness on the surface and softness inside encourages this investigation to measure hardness experimentally and theoretically.